Kewarisan Tanah Pusako Tinggi dalam Perspektif Hukum Adat dan Hukum Islam - Nining Gilang Sari (Universitas Sains dan Teknologi Komputer, 2024)
The inheritance of high pusako land from the perspective of Minangkabau customary law and Islamic law is an interesting topic to investigate because Minangkabau is one of the communities in Indonesia that adheres to a matrilineal kinship system which is closely related to the inheritance system. This article discusses the concept of inheritance of Pusako Tinggi land from two different legal perspectives. In Minangkabau customary law, the concept of inheritance of high pusako land is divided into three types: high inheritance, low inheritance, and search property. Management of high inheritance assets is in the hands of the woman or mother, supervised by the mamak, and may not be owned privately. Disputes regarding the use of inheritance can be resolved through the Nagari Customary Meeting. On the other hand, Islamic law has its own rules regarding inheritance of property. The Compilation of Islamic Law regulates the distribution of inheritance between heirs in different proportions according to the kinship relationship with the heir. Case studies of high inheritance land disputes show how the courts consider customary law and Islamic law in resolving these disputes. The court stated that selling high heritage land without the consent of all family members was an unlawful act according to Minangkabau customs. With a better understanding of these two legal perspectives, it can be hoped that the resolution of Pusako Tinggi land inheritance disputes will be fairer and in accordance with prevailing cultural and religious values.